Evaluasi Penerapan Tata Kelola TI Menggunakan Cobit 5 - Adi Wibowo (LPPM Universitas Muhammadiyah Kotabumi, 2020)
The quality of Academic Information System Service (SIAKAD) which has been implemented by STIH Muhammadiyah Kotabumi has not been optimal as expected. In accordance with that, it was seen that there is incompatibility between the plan and the reality. An audit related to the maturity level of TI management on the implementation of SIAKAD STIH Muhammadiyah Kotabumi is important to be conducted in order to get the recomendation of service improvement. Evaluation was done through questionaire, interview and document of STIH Muhammadiyah Kotabumi. This research used COBIT 5 consisting of EDM 04, APO04, APO 07, BAI 04, DSS 01, dan MEA 01. The data source was gotten from the Head of STIH Muhammadiyah Kotabumi, the Head of administrations, the Head Communication Centre, TI Staff, and Academic Staff. An analysis was done by using descriptive interpretative based on COBIT 5.